The Improving Global Health fellowship: a qualitative analysis of innovative leadership development for NHS healthcare professionals - Alexandra Monkhouse; Leanne Sadler; Andrew Boyd; Fleur Kitsell (BMC, 2018)
Abstract Background The importance of leadership development in the early stages of careers in the NHS has been highlighted in recent years and many programmes have been implemented which seek to develop leadership skills in healthcare professionals. The Improving Global Health (IGH) Fellowship scheme is one such programme, it provides a unique leadership development opportunity through an overseas placement with a focus on quality improvement work. This evaluation examines the impact of completing an IGH Fellowship on the career and leadership development of participants, who are referred to as Fellows. Methods Fellows who had returned from overseas placement between August 2008 and February 2015 were invited to complete an anonymised online questionnaire, which collected information on: demographic details, motivations for applying to the programme, leadership development and the impact of the IGH Fellowship on their career. Fifteen semi-structured interviews were conducted to further explore the impact of the programme on Fellows' leadership development and career progression. Interview transcripts were manually coded and underwent thematic content analysis. Results The questionnaire had a 67% (74/111) response rate. The number of fellows who self-identified as a leader more than doubled on completion of the IGH Fellowship (24/74 pre-fellowship versus 58/74 post-fellowship). 74% (55/74) reported that the IGH Fellowship had an impact upon their career, 35 of which reported that the impact was "substantial". The themes that emerged from the interviews revealed a personal development cycle that consolidated the fellows' interests and values whilst enhancing their self-efficacy and subsequently impacted positively upon their career choices. Three interviewees expressed frustration at the lack of opportunity to utilise their new skills on returning to the United Kingdom (UK). Conclusions The IGH Fellowship successfully empowered healthcare professionals to self-identify as leaders. Of the 45/74 respondents who commented on the impact of the IGH Fellowship on their career, 41/45 comments were positive. The fellows described a process of experiential learning, reflection and evolving cultural intelligence, which consolidated their interests and values. The resultant increase in self-efficacy empowered these returned fellows in their choice of career.